Penerapan Penggunaan Media Digital Dalam Menumbuhkan Kesadaran Budaya Baca Siswa - Ade Falah (PEDAGOGIA : JURNAL KEGURUAN DAN PENDIDIKAN, 2025)
The application of digital media in education has great potential to increase students' reading culture awareness. This study aims to evaluate the effectiveness of using digital media in fostering students' reading culture awareness. This research is a quantitative study with a descriptive approach. The data source consisted of fourth grade students at SDN Gresik, who had participated in the digital literacy programme for one semester. Data were collected through questionnaires, interviews and observations. The results showed that the use of digital media significantly increased students' reading culture awareness. The average time students spent reading increased by 30% and 80% of students felt more motivated to read. In addition, the digital literacy programme successfully involved parents and teachers in supporting students' reading habits at home. These findings show that digital media can provide easy and interesting access to reading materials and create a supportive environment for students' reading habits. Thus, the application of digital media in fostering students' reading culture awareness can be an effective strategy to achieve quality education in the digital era.